Bahasa Indonesia: Bahasa Indonesia - Pradana, Charis Rizqi (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2022)
The focus of this research is (1) How is the process of applying adaptive assertive techniques to foster adaptive abilities in adolescents (2) How is the application of adaptive assertive techniques to foster adaptive abilities in adolescents . To describe these problems, researchers used a qualitative descriptive approach. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is descriptive analysis. From the results of data analysis it can be concluded that REBT with Adaptive Assertive Techniques to Grow Adaptive Capabilities in Adolescents is carried out in 5 steps, namely helping problems, diagnosis, prognosis, therapy/medication, evaluation/follow-up. After the counseling process has been carried out, there are several impacts from the application of adaptive assertive techniques to the counselee where the counselee's ability to adapt is increasing. The counselee is able to control himself when the counselee feels difficulty in adaptation